Professing darkness: Cormac McCarthy's Catholic critique of American enlightenment - DeCoste, D. Marcel (Louisiana State University Press, 2024)
"Professing Darkness: Cormac McCarthy's Catholic Critique of American Enlightenment establishes the centrality of Catholic thought, imagery, and sacrament both to the spiritual outlook of the McCarthy corpus and, more specifically, to its critique of Enlightenment values and their realization in American history. To this end, D. Marcel DeCoste surveys McCarthy's fiction from both his Tennessee and southwestern periods, with chapters devoted to eight of his published novels-from Outer Dark to The Road-and an introduction and coda that offer analyses of two of his dramatic works, along with his final novels, The Passenger and Stella Maris. The argument advanced by DeCoste is twofold. First, his readings demonstrate that McCarthy's work mounts a sustained critique of core Enlightenment values and their bloody results in the American context. Second, he establishes that this critical engagement with American Enlightenment is one enabled by, and articulated through, specifically Catholic teachings on such topics as sacraments, ethics, and material creation. Though other studies trace how McCarthy's fiction dissects such American myths as radical individualism and Manifest Destiny, they do not, at the same time, take up the question of how the fiction's spiritual interests and obtrusive Christian symbolism relate to this critical project. More than merely calling attention to McCarthy's own religious background or his drawing on sacramental language, DeCoste examines the significance of Catholicism to the author's depictions not just of religion and ethics, but of the modernity many critics see McCarthy as critiquing. Throughout Professing Darkness, DeCoste offers extended analysis of McCarthy's engagement with American history and myth, early modern and Enlightenment thought, and Catholic theology, ethics, and sacramentalism"--